Red Platoon : a true story of American valor - Romesha, Clinton (Dutton, 2016)
An account of the horrendous October 2009 attack on the American Combat Outpost Keating in Afghanistan, told in a frank, engaging vernacular by the staff sergeant and Medal of Honor winner. Romesha ably captures the daily dangers faced by these courageous American soldiers in Afghanistan.--